It's a beautiful day in the neighborhood: Overcoming barriers regarding children's mental health against help-seeking via community social capital. Issue 3 (27th May 2021) - Smith, Cassidy; Ashdown, Brien K.; Dixe, Alessa; Guarnaccia, Joey
ABSTRACT: One in five children suffers from mental illness, yet estimates suggest that for various reasons, 50%-70% of these children are not receiving sufficient care. This study examines how mental illness stigma and parents' help-seeking for their children interact with community social capital and demographic factors. Parents ( N = 104) of children ages three to eight in the Northeastern USA completed a questionnaire that included measures of social capital, mental illness stigma, help-seeking attitudes, and children's current psychosocial symptoms. The lowest rate of mental illness was among children of high SES. Most children in need were not receiving treatment, which is likely a result of parents not recognizing the symptoms of mental illness. Greater social capital was associated with less stigma and more positive attitudes toward help-seeking. These findings suggest that interventions focused on increasing parents' knowledge of mental health and increasing social capital within the community will increase effective parental help-seeking for children.